FACTOR RELEATED OF ANTI-TUBERCULOSIS DRUG RESISTENCY ON PULMONARY TUBERCULOSIS PASIENT IN LABUANG BAJI HOSPITAL MAKASSAR - Saleh, Sapriadi; Syahridha, Syahridha (Indonesian Journal of Tropical and Infectious Disease, 2018)
Tuberculosis become crucial diseases in the world. The disease can spread rapidly since it spreads through the air. The transmission through coughing and sneezing from droplet TB Patients. Containing Mycobacterium tuberculosis can be exposed to anyone who is around the patient. The aim of this research is to analyze the factors that affect the anti-tuberculosis drug resistance in patients with pulmonary tuberculosis in Labuang Baji Hospital Makassar. The research design is cross sectional approach. This study is conducted in June–July 2017 with a total sample of 60 respondents. Based on the data analysis, it is found that there were 34 respondents (56.7%) from 15–34 years old group and 26 respondents (43.3%) from 35–54 years old group. There were 35 female respondents (58.3%) and 25 male respondent(41.7%), is respondents with positive VCT test result and 45 respondensts (74.0%) with negatif VCT test, 54 respondents (90,0%) who have treatment history previously, 45 respondents (78.3%) have history with TB contact, 45 respondents (75.6%) who had good knowledge. 51 respondents (95%) with anti tuberculosis drug resistance. The result of statistical test using Chi-Square test is showed that there was a significant correlation between treatment history and anti tuberculosis drug resistance with p = 0.024 < α = 0.05. But, there was no relationship between sex and knowledge with anti tuberculosis drug resistance with p value 0.56 and 0.566 (p value > α = 0.05). It is recommended to health worker to give health education for patient and their family, so they can do their treatment until the patients are cured. It can prevent the patient to be anti tuberculosis drug resistance patient.